2021
DOI: 10.1158/1541-7786.mcr-20-0967
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of N-Linked Glycans as Potential Biomarkers of Clinical Course in Human Prostate Cancer

Abstract: Prostate cancer is the most common cancer in men worldwide. Despite its prevalence, there is a critical knowledge gap in understanding factors driving disparities in survival among different cohorts of patients with prostate cancer. Identifying molecular features separating disparate populations is an important first step in prostate cancer research that could lead to fundamental hypotheses in prostate biology, predictive biomarker discovery, and personalized therapy. N-linked glycosylation is a cotranslationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The N -glycan spatial profiling using matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) has emerged over the past few years as a powerful approach in clinical research for insight into aberrant N -glycan structures in specific cell types and histopathological regions during disease progression (Carter et al, 2020 ; Conroy et al, 2021 ; Grzeski et al, 2022 ; Malaker et al, 2022 ; Zhang et al, 2022 ). The method relies on spraying the enzyme peptide N -glycanase (PNGase) over formalin-fixed paraffin-embedded (FFPE) tissue sections to in-situ release the N -linked carbohydrates from their carrier proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The N -glycan spatial profiling using matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) has emerged over the past few years as a powerful approach in clinical research for insight into aberrant N -glycan structures in specific cell types and histopathological regions during disease progression (Carter et al, 2020 ; Conroy et al, 2021 ; Grzeski et al, 2022 ; Malaker et al, 2022 ; Zhang et al, 2022 ). The method relies on spraying the enzyme peptide N -glycanase (PNGase) over formalin-fixed paraffin-embedded (FFPE) tissue sections to in-situ release the N -linked carbohydrates from their carrier proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Here, high mannose glycans were found to be abundant in tumor regions as well as increased tri-and tetraantennary glycans that increased proportionally with tumor grade (19). Furthermore, the triantennary glycan at 2,320 m/z was found to be highly abundant in patients with biochemical recurrence and was correlated with decreased survival by Kaplan-Meier analysis (19). Although not global approaches, several historical studies have utilized human PCa tissue to survey presence or absence of Lewis antigens which are highly associated with malignant transformation (20)(21)(22)(23)(24).…”
Section: Broad Changes In N-glycosylation Associated With Pcamentioning
confidence: 86%
“…Here, a human PCa tissue block with both tumor and non-tumor regions was analyzed and it was shown that high mannose glycans (Man5-Man9) were particularly evident in the tumor regions compared to adjacent benign and stroma while multiple biantennary non-sialylated glycans were detected primarily in non-tumor regions (18). A recent study utilized MALDI-IMS to profile a tissue microarray containing prostate tumor tissue (n = 108) and benign tissue (n = 30) from 138 patients (19). Here, high mannose glycans were found to be abundant in tumor regions as well as increased tri-and tetraantennary glycans that increased proportionally with tumor grade (19).…”
Section: Broad Changes In N-glycosylation Associated With Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the glycome, which comprises all of the sugar polymers (glycans) synthesized by cells, has remained relatively unexplored in many cancer settings including PCa despite the fact that aberrant glycosylation is a well-known hallmark of cancer [10] and the prostate is a major secreter of glycoproteins [11]. So far, studies on the PCa tumor glycome [12][13][14] have only evaluated early stage disease or, in the setting of CRPC, changes in the serum glycome [15,16], mostly because advanced PCa tissue is usually not available because the tissue is rarely biopsied or resected at this stage of the disease. Unfortunately, changes in the serum glycome are not necessarily tumor derived as systemic hormonal therapy has effects on many tissue types.…”
Section: Introductionmentioning
confidence: 99%